2016
DOI: 10.1098/rsos.160112
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of tyrosine side chain in neurotoxic Aβ differs in two different secondary structures of the peptide

Abstract: Amyloid β (Aβ) peptide is present as a major component in amyloid plaque that is one of the hallmarks of Alzheimer's disease. The peptide contains a single tyrosine residue and Aβ has a major implication in the pathology of the disease progression. Current investigation revealed that the tyrosine side chain attained two different critical stereo orientations in two dissimilar conformational states of the peptide. The extended α-helical structure of the peptide observed in an apolar solvent or methanol/water mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
3
3
0
Order By: Relevance
“…It is found that aromatic residues of the peptide such as Phe4 and Tyr10 drive the trajectories of these systems to different conformations depending on their initial stacking interactions with the BNNT surface. The importance of the tyrosine residue in amyloid formation was also reported in other studies. The calculated free-energy landscapes reveal a single deep minimum at small R g value for the solvated Aβ(1–42) without any nanoparticles, a wide basin at large R g value for the Aβ(1–42) peptide with BNNS, and a rather complex surface with more localized states for the peptide in the presence of (12,12) BNNT.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is found that aromatic residues of the peptide such as Phe4 and Tyr10 drive the trajectories of these systems to different conformations depending on their initial stacking interactions with the BNNT surface. The importance of the tyrosine residue in amyloid formation was also reported in other studies. The calculated free-energy landscapes reveal a single deep minimum at small R g value for the solvated Aβ(1–42) without any nanoparticles, a wide basin at large R g value for the Aβ(1–42) peptide with BNNS, and a rather complex surface with more localized states for the peptide in the presence of (12,12) BNNT.…”
Section: Discussionsupporting
confidence: 79%
“…Tyr10 is the only tyrosine residue in the Aβ(1–42) sequence, and it plays a critical role in β-sheet exposure. The importance of Tyr10 was also reported in some of the earlier studies. …”
Section: Results and Discussionsupporting
confidence: 67%
“…15,16 The p-p interaction energies and tyrosine (Y)-mediated two-dimensional peptide assembly morphology were reported via quantum calculation or two-dimensional imaging method. [17][18][19][20] The single Y-containing active sequences (LYQLEN from the human insulin chain A, 21 NNQQNY from the yeast prion protein Sup35, [22][23] and VQIVYK from the tau protein [24][25][26] ), known to form ordered oligomers with b-strand structures that mature into fibril structures, have been investigated to better understand the p-p stacking interaction. The collision-induced dissociation (CID)-MS/MS was used to study the oligomer structures of the LYQLEN, NNQQNY, and VQIVYK sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies employing MD analysis and focusing on rotamers often represented their data via plotting changes in c dihedral angles over time (7,8) or through principal component analysis (9). Although few dihedral angles are easy to plot, a simple classification scheme is required when dealing with large number of heterogeneous residues.…”
Section: Introductionmentioning
confidence: 99%